Effect of harvesting management on grain yield of rapeseed from 1980 to 1983 - Santos, Henrique dos; Pereira, Luiz Ricardo; Lhamby, Júlio Cesar B.; Nedel, Jorge Luiz (Pesquisa Agropecuaria Brasileira, 2014)
The effect of harvesting methods (manual, windrow and direct with a combine) and harvesting times (number of days after flowering) on yield of rapeseed (Brassica napus L. var. Oleifera Metzg.), was evaluated during four years at the Centro Nacional de Pesquisa de Trigo (CNPT), in Passo Fundo, RS, Brazil. Cultivar CTC 4 was conventionally seeded each year on an area of about one hectare. In 1981 and 1982 the manual and windrow harvesting methods gave the highest grain yields, between 54 and 69 days after flowering and with grain moisture content of 22% to 42%. In 1981 direct harvesting with a combine gave the best grain yields, between 68 and 74 days after flowering, with grain moisture content of 8% to 10%. Climatic conditions (rain, insolation and wind) at the time of harvesting with a combine appeared to increase pod dehiscence and decrease grain yield.